Work stress, technological changes, and job insecurity in the retail organization context - Ghani, Bilqees; Memon, Khalid Rasheed; Han, Heesup; Ariza-Montes, Antonio; Arjona-Fuentes, Juan M. (Frontiers in Psychology, 2022)
The study intends to investigate the relationships between work stress and job insecurity as well as technological changes and job insecurity, with job satisfaction acting as a mediator. The study was conducted among Pakistani retail industry employees using survey questionnaires distributed online and in stores. The sample size was comprised of 262 retail workers from the FMCG and shopping mall industries. The responses were screened using the statistical software tool SPSS, and hypotheses were examined through SMART-PLS. The findings show that work stress has a strong relationship with job insecurity; additionally, the relationship appears statistically significant (β= 55.7%, p 0.05), indicating that there is an increased level of job insecurity if work stress is increased. However, technological advancements showed less influence on job insecurity and had statistically insignificant results (β=5.9%, p>0.05). This demonstrates that many technological changes cause high levels of job insecurity because employees fear they will be unable to cope with the changing environment. Furthermore, the mediating mechanism of job satisfaction was found to be significant, as employees with lower levels of satisfaction reported higher levels of insecurity, aiding in the narrowing of the gap in this section of the study. The study also has practical implications because the results show that the retail industry needs to act quickly to make sure workers don't worry about losing their jobs, especially now that COVID-19 is spreading like wildfire.